ENTREVISTA COM OLE SKOVSMOSE - Firme, Ingrid Cordeiro; Shintani, Rodolfo Masaichi; Tonéis, Cristiano Natal (Educere et Educare, 2020)
The interview with Professor Ole Skovsmose was held on May 7, 2019, at the Department of Mathematics Education of the State University of São Paulo, UNESP, in the city of Rio Claro, São Paulo. Professor Skovsmose holds a master’s degree in Philosophy and Mathematics from the University of Copenhagen (1975) and a PhD in Mathematics Education from the Royal Danish School of Educational Studies (1982). His professional career began at the Royal Danish School of Educational Studies in Copenhagen, where he worked as a full professor from 1996 to 1999. From 1999 to 2009 he worked at the University of Aalborg, where he retired. He remains as emeritus professor of this institution until the present day. He is also a contributing professor at UNESP, Rio Claro, working as a teacher and adviser in the Postgraduate Program in Mathematics Education. In the interview transcribed in this dossier, Skovsmose talks about the Philosophy of Mathematics Education, about the work he has developed in Africa and about his interest in studying and working with Philosophy of Mathematics Education and with Critical Mathematics Education.